A Mediation Analysis of Sex Motives in the Locus of Control-Risky Sexual Behaviour Nexus among Students in Ugandan Universities - Winfred Biribonwa Kyosaba; David Kani Olema; Aloysius Rukundo (THE UGANDA HIGHER EDUCATION REVIEW, 2025)
This study investigates the psychological and behavioural dynamics influencing risky sexual behaviours (RSBs) among young adults in Ugandan universities during their critical transition to adulthood. A quantitative research design was employed using a self-administered questionnaire to examine the interplay between locus of control (LOC), sex motives (SMs), and risky sexual behaviours (RSBs) among 527 randomly selected students (250 males, 277 females) from four universities in Uganda. Results indicated that 78.2% of participants exhibited a strong external LOC, correlating with heightened RSB engagement (65.7%), including unprotected sex (38.3%), multiple partners (26.4%), early sexual debut (12.1%), and homosexual practices (7.8%). While sexual motives were generally moderate (e.g., intimacy, coping), peer approval emerged as notably low (M = 9.08, SD = 4.26). Mediation analysis revealed that SMs – particularly self-affirmation and partner approval – significantly mediated the LOC-RSB relationship (R² = 20%, p < 0.02), suggesting that students with external LOC often engage in RSBs to fulfil psychological needs. These findings align with the Theory of Planned Behaviour (TPB), emphasising how perceived behavioural control and intrinsic motivations shape sexual decision making. The study highlights the need for targeted interventions, including (1) empowerment programmes to cultivate internal LOC and self-efficacy, (2) peer-led education addressing normative beliefs about sex motives, and (3) youth-friendly health services to improve access to contraceptives and counselling. By integrating psychological and social determinants, universities can mitigate RSB risks and promote sexual health
Keywords: Risky sexual behaviours; Locus of control; Sex motives; Young adults; Interventions.